A scalable distributed system based on microservices for collecting pod logs from a Kubernetes cluster - Lisboa, Flávio Gomes da Silva (Anais do Congresso Latino-Americano de Software Livre e Tecnologias Abertas (Latinoware); 2021: Anais do XVIII Congresso Latino-Americano de Software Livre e Tecnologias Abertas, 2021)
This article presents the architecture of a distributed log collection system for Kubernetes clusters. Initially, we present the motivation for creating the system. Then, we present an overview of the system, consisting of several microservices. Next, we approach the implementation of each of the microservices. All system components are free and open software. This article is an example of how a distributed system with microservices can be heterogeneous in relation to the programming languages used.